A Framework for Integrated E-notary Services Based on Blockchain for Civil Law Notaries: The Case of Indonesia - Putra, Panca O. Hadi; Muda, Iskandar; Bakry, Mohammad Ryan; Yusuf, Chandra; Santosa, Irwan (Society of Visual Informatics, 2025)
The trend of digitalization has called for electronic notary services that are both efficient and secure. This study proposes a framework for an integrated e-notary system using blockchain technology based on Indonesia's civil laws and regulations. To accomplish this objective, this study uses a methodology combining both normative legal and information systems methods. This study starts with a search of existing laws and regulations conducted on the Indonesian government regulation database (peraturan.go.id). Subsequently, laws and regulations are analyzed to elicit system components and functional requirements. The findings are visualized using a rich picture, resulting in a framework for an integrated e-notary system. The system entails a blockchain network in which Indonesian registered notaries act as nodes. The proposed system is integrated with other e-government systems to facilitate notarial services as required by laws and regulations, such as document validity checks, electronic recording and storage of notarial deeds, document legalization, and notary protocol archiving. To support the proposed blockchain-based e-notary system, this study suggests several regulatory adjustments based on legal gaps identified using Kostruba’s approach. Regulatory adjustments include creating technical regulations on the establishment of the blockchain network operated by the Indonesian Notary Association (INI) and also the creation and storage of notarial deeds electronically. The findings imply that the proposed e-notary system has the potential to enhance notary services’ security and efficiency in Indonesia, though successful implementation of such a system may hinge upon the readiness of the stakeholders.